Desenvolvimento de aplicativo para a gestão de cerimoniais públicos em Câmaras de Vereadores - Schimanko, Alexandra Ribeiro de Souza (2021)
This dissertation has as its object of study communication as a fundamental and strategic part in public administration and a tool that enhances relationships, allowing for a dialogic exchange between different subjects and emphasizing the public character while enabling the monitoring of the change of a social reality and approaches interests of the community. This investigation seeks to understand the communication systems in the City Councils, with the public ceremonial being the highlight of this study. Therefore, the research problem investigated is: how can public ceremonial, practiced in City Councils, be optimized through a mobile application? The general objective of the research is, therefore, to determine how an application (mobile/for mobile devices) can enhance communication systems in City Councils by optimizing public ceremonial. To do so, we sought to: develop a mobile application to optimize public ceremonial in City Councils; select the public ceremonial activities practiced in the City Councils; identify audiences impacted by public ceremonial activities in City Councils; validate the use of the application as an innovative system in City Councils and optimizer public ceremonial practices in these organizations. The theoretical framework brings reflections on systemic thinking, drawing on concepts from the theories of systems, communication and organizations. In addition, it brings a reflection on public management and information systems, and also on communication innovation systems, where public ceremonial is inserted. The study carried out is characterized as applied and experimental research, observing the interface and interaction design techniques for the development of the mobile application. The mapping of audiences, protocol events and legislation involved in the entire process was carried out in order to then develop the mobile application. From the development stage, its prototyping and its final version were presented, as well as the application's testing. The test results showed the ease and difficulties of users when trying out the application, its mechanisms and interfaces, as well as using it in a simulated official ceremony. From the difficulties pointed out, it was possible to identify the requirements to propose improvement of the system and development of actions that encourage further research on the subject. Finally, the validation of a primary need in the Municipal Legislative Houses to optimize the scripting of ceremonial and protocol rituals is presented, a movement that brings the population closer to the City Council and gives space for communication to exercise its strategic role of clarifying about the real social and political functions of the institution, especially with regard to the representation exercised by councilors and the exercise of citizenship and democracy.